SPECIFICITY OF DEVELOPMENT OF IDENTITY OF YOUNG CITIZENS IN CONDITIONS OF SOCIAL TRANSFORMATIONS - Когiakovtseva, Olga; Timonin, Andrey; Bugachuk, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
In the article the problems of formation of civil identity of the youth as the most important condition of effective development of post-industrial society. The authors analyze the main approaches to the formation and development of citizenship in an era of socio-economic and political transformations. Proof of the urgency of the problem mentioned in the article are the results of psychosemantic study of national identity of students.